Enhancement of anti-corrosion properties of titanium alloy by using dip-coating of poly (Caprolactone) hydroxyapatite composite [electronic resource] - Mohd. Faiz Mohd. Yusoff, 1988- author (2014)
Thesis (Sarjana Kejuruteraan Bioperubatan) - Universiti Teknologi Malaysia, 2014